A Rare Case of Glossopharyngeal Neuralgia due to Neurovascular Conflict - Marc Vecchi; Ricardo Pereira Mestre; S. Luciamma Thiekalamuriyil; Roberto Cartolari (Case Reports in Neurology, 2018)
In the context of painful cranial neuropathies, a very rare cause is represented by the irritation of the glossopharyngeal nerve due to various aetiologic factors. Here, we present a case of neuralgia of the ninth right cranial nerve due to a compression of its nerve root upon the kinking of the homolateral vertebral artery, resulting in a disabling clinical overview for the patient. Our objective was to focus the reader’s attention on the clinical manifestation, which alone could lead to an immediate diagnosis. The imaging and laboratory studies proved to be fundamental in diagnosing the causes, yet the knowledge of the symptoms and the signs of this rare clinical entity can prevent misdiagnosis, mismanagement and consequent economic expenditure as occurred in the case described here.